Energetically unfavorable amide conformations for N6‐acetyllysine side chains in refined protein structures1. Issue 6 (25th February 2013) - Genshaft, Alexander; Moser, Joe‐Ann S.; D'Antonio, Edward L.; Bowman, Christine M.; Christianson, David W.
Abstract The reversible acetylation of lysine to form N6‐acetyllysine in the regulation of protein function is a hallmark of epigenetics. Acetylation of the positively charged amino group of the lysine side chain generates a neutral N‐alkylacetamide moiety that serves as a molecular "switch" for the modulation of protein function and protein–protein interactions. We now report the analysis of 381 N6‐acetyllysine side chain amide conformations as found in 79 protein crystal structures and 11 protein NMR structures deposited in the Protein Data Bank (PDB) of the Research Collaboratory for Structural Bioinformatics. We find that only 74.3% of N6‐acetyllysine residues in protein crystal structures and 46.5% in protein NMR structures contain amide groups with energetically preferred trans or generously trans conformations. Surprisingly, 17.6% of N6‐acetyllysine residues in protein crystal structures and 5.3% in protein NMR structures contain amide groups with energetically unfavorable cis or generously cis conformations. Even more surprisingly, 8.1% of N6‐acetyllysine residues in protein crystal structures and 48.2% in NMR structures contain amide groups with energetically prohibitive twisted conformations that approach the transition state structure for cis‐trans isomerization. In contrast, 109 unique N‐alkylacetamide groups contained in 84 highly accurate small molecule crystal structures retrieved from the Cambridge Structural Database exclusively adopt energetically preferred trans conformations. Therefore, we conclude that cis and twisted N6‐acetyllysine amides in protein structures deposited in the PDB are erroneously modeled due to their energetically unfavorable or prohibitive conformations. Proteins 2013; © 2012 Wiley Periodicals, Inc.